2016
DOI: 10.1007/s00359-016-1101-4
|View full text |Cite
|
Sign up to set email alerts
|

Innate colour preferences of the Australian native stingless bee Tetragonula carbonaria Sm.

Abstract: Innate preferences promote the capacity of pollinators to find flowers. Honeybees and bumblebees have strong preferences for 'blue' stimuli, and flowers of this colour typically present higher nectar rewards. Interestingly, flowers from multiple different locations around the world independently have the same distribution in bee colour space. Currently, however, there is a paucity of data on the innate colour preferences of stingless bees that are often implicated as being key pollinators in many parts of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 88 publications
1
67
1
1
Order By: Relevance
“…Further studies are underway to test for the effect of abiotic environmental stresses, such as evapotranspiration and resource limitation For I. pumila, the role of pollinators, particularly bumblebees, appeared to be more ambiguous since we detected a stabilizing selection mediated by pollinator's choice for the blue morph only. Some studies have reported that bumblebees have an innate colour preference for the blue range of wavelengths (Lunau andMaier 1995, Smithson andMacnair 1996), a pattern observed in other bees species (Dyer et al 2016). Such innate colour bias is expected to guide them to explore blue flowers in preference to other natural objects within a landscape.…”
Section: Discussionmentioning
confidence: 96%
“…Further studies are underway to test for the effect of abiotic environmental stresses, such as evapotranspiration and resource limitation For I. pumila, the role of pollinators, particularly bumblebees, appeared to be more ambiguous since we detected a stabilizing selection mediated by pollinator's choice for the blue morph only. Some studies have reported that bumblebees have an innate colour preference for the blue range of wavelengths (Lunau andMaier 1995, Smithson andMacnair 1996), a pattern observed in other bees species (Dyer et al 2016). Such innate colour bias is expected to guide them to explore blue flowers in preference to other natural objects within a landscape.…”
Section: Discussionmentioning
confidence: 96%
“…Marker points of bee‐ and hummingbird‐flowers were frequently closer to the wavelengths of maximal spectral discrimination of their main pollinators, similar to previous studies (Dyer et al ., ; Shrestha et al ., ). Hummingbird‐flowers reflected more and presented more marker points at long wavelengths (red band), whereas bee‐flowers reflected and presented more marker points at short and medium wavelengths (UV and blue bands) in accordance with bees’ visual sensitivity and colour preferences (Chittka et al ., ; Dyer et al ., ). We also found that marker points of bee‐flowers were significantly closer to the optimal wavelength for colour discrimination in bees, mainly at 400 nm, confirming that colours of bee‐flowers are better discriminated by bees than are colours of hummingbird‐flowers.…”
Section: Discussionmentioning
confidence: 97%
“…We surveyed categorical and quantitative variables previously described as important visual signals for target detection and discrimination by bees and birds (Spaethe et al, 2001;Cazetta et al, 2009;Dyer et al, 2016;Bukovac et al, 2017;van der Kooi et al, 2018). We considered as categorical variables the presence of colour patterns, floral guides and UV patterns ( Fig.…”
Section: Colour Variablesmentioning
confidence: 99%
“…Several studies have described spontaneous colour preferences in bees (Lunau 1990;Giurfa et al 1995;Chittka et al 2004;Dyer et al 2016), butterflies (Ilse 1928;Swihart and Swihart 1970;Weiss 1997;Kinoshita et al 1999;Kandori et al 2009;Blackiston et al 2011), moths (Kelber 1996;Goyret et al 2008), and hoverflies (Lunau and Wacht 1994). The aims of the present study were to explore a comparative approach with bees and to identify potential differences in spontaneous colour responses between temperate and tropical bees, comparing the responses of three social bee species that were tested under the same conditions.…”
Section: Discussionmentioning
confidence: 99%